Morphodynamics: Rivers beyond steady state. Issue 4 (26th April 2015) - Church, M.; Ferguson, R. I.
Abstract: The morphology of an alluvial river channel affects the movement of water and sediment along it, but in the longer run is shaped by those processes. This interplay has mostly been investigated empirically within the paradigm of Newtonian mechanics. In rivers, this has created an emphasis on equilibrium configurations with simple morphology and uniform steady flow. But transient adjustment, whether between equilibrium states or indefinitely, is to be expected in a world in which hydrology, sediment supply, and base level are not fixed. More fundamentally, water flows and all the phenomena that accompany them are inherently unsteady, and flows in natural channels are characteristically nonuniform. The morphodynamics of alluvial river channels is the striking consequence. In this paper, we develop the essential connection between the episodic nature of bed material transport and the production of river morphology, emphasizing the fundamental problems of sediment transport, the role of bar evolution in determining channel form, the role of riparian vegetation, and the wide range of time scales for change. As the key integrative exercise, we emphasize the importance of physics‐based modeling of morphodynamics. We note consequences that can be of benefit to society if properly understood. These include the possibility to better be able to model how varying flows drive morphodynamic change, to understand the influence of the sediments themselves on morphodynamics, and to recognize the inherent necessity for rivers that transport bed material to deform laterally. We acknowledge pioneering contributions in WRR and elsewhere that have introduced some of these themes. Key Points: River morphodynamics is the consequence of bed material supply and transport Lateral instability is an inherent feature of river morphodynamics Riparian vegetation is a significant mediator of morphodynamics